The Effect of Teaching Program on the Development of Disabled Students, Self – Concept - Rajeh Harb (My University, 2010)
The purpose of this study was to investigate the effect of teaching program on the development of disabled students, self – concept. The sample of this study consisted of 28 male and female disabled students. They participated in a 6 – week teaching program and completed a self – concept survey developed by the researcher. The results showed that the teaching program had appositive effect on the self – concept of the disabled students. The researcher recommended giving more attention to the self – concept in the educational programs.

هدفت الدراسة إلى التعرف إلى أثر برنامج تعليمي في تنمية مفهوم الذات لدى مجموعة من الطلبة المعاقين حركيا وللتحقق من ذلك قام الباحث بتصميم استبانة لقياس مستوى مفهوم الذات، وكذلك قام الباحث بتصميم برنامج تعليمي لتعليم بعض مهارات الريشة الطائرة للمعاقين حركياً، وقد تضمنت العينة (28) طالب وطالبة من ذوي الإعاقات الحركية، وطبق عليهم البرنامج التعليمي لمدة 6 أسابيع وأجابوا على مقياس مفهوم الذات الذي أعده الباحث وأجرى عليه دلالات الصدق والثبات. وأظهرت النتائج أن البرنامج التعليمي قد أثر بشكل ايجابي على مفهوم الذات لدى الطلبة المعاقين. وقد أوصى الباحث بإعطاء موضوع مفهوم الذات أهمية في البرامج التعليمية.
أثر برنامج تعليمي في تنمية مفهوم الذات لدى مجموعة من الطلبة المعاقين حركياً